IN SILICO ANALYSIS OF ACRAL PEELING SKIN SYNDROME: A PROTEOMIC APPROACH - Desai, Dignya; Modi, Vaibhav; Datta, Manali (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Acral peeling skin syndrome (APSS), a rare genetic disorder, indicated by the continuous blistering and shedding of the outer epidermal layers. Transglutaminase 5 (TGM5), a calcium-dependent TGM, present in the epidermis has been implicated as the cause of APSS. An attempt has been made to compare in silico the wild and mutant form of TGM5 and its implication on its interaction with involucrin (IVL). Methods: Comparative modeling was performed using MAESTRO for proteins TGM5 and IVL using templates from the protein databank. Generated model was later refined using side chain refinement and loop refinement. Three-dimensional (3D) structure of TGM5 and IVL was analyzed in PROCHECK, VERIFY3D, and ERRAT was used to assess the reliability of the 3D model. IMPACT package from Schrödinger was used to generate a binding site for calcium ion which is essential for functioning of protein. Energy minimization for the modelled structures was performed using IMPACT module of Schrodinger. Subsequently, wild type and mutated models of TGM5 was used for performing docking studies with IVL. Results: The structures for TGM5 and IVL were modeled and energy minimized using Schrödinger suite. Conserved calcium binding domain formed by three asparagine residues (N224, N226 and N229) and alanine (A221) corresponding to TGM3 was found in TGM5 at positions 226, 229, 231, and 234. Identification of probable active site for TGM5 was predicted using SiteMap program in Schrödinger. 17 cysteine residues are present in wild type structure of TGM5 and in mutated form G113C, the probability of forming an extra disulfide increases. With the mutation occurring at 113 position formation of disulfide bond between C113 and Cys306 increases manifold. This hypothesis was confirmed by the fact that root-meansquare distance value of energy minimized mutated TGM5 when compared to native TGM5 on aligning all 561 atoms was found to be 0.141 indicating a change of overall structure of protein. Conclusion: The mutation G113C is increasing the dynamic nature of the protein to increase as the probability of the formation of disulfide bond increases. Keywords: Skin, Acral peeling skin syndrome, Glutaminase, Involucrin, Mutation, Interaction.